Figure 2 from Integrated Molecular Characterization of Patient-Derived Models Reveals Therapeutic Strategies for Treating CIC-DUX4 Sarcoma - Marianna Carrabotta (8193039) (2025)
CDS PDX models recapitulated the phenotypic characteristics and transcriptional profiles of the primary tumor. A, Histologic and IHC features of CDS patient samples and corresponding PDXs at different in vivo passages (P1, first passage; P3, third passage). Sections were stained with hematoxylin-eosin (H&E) or with antibodies against the antigens ETV4 and CD99. Bar, 100 μm. B and C, Spearman correlation analysis among the gene expression profiles of CDS tumors, their corresponding PDX models (P3), and the PDX-derived cell lines are shown based on the signatures of 3,179 (B) and 71 (C) DEGs. Correlation coefficients are shown.